Association between gaps in antihypertensive medication adherence and injurious falls in older community-dwelling adults: a prospective cohort study. Issue 3 (4th March 2019) - Dillon, Paul; Smith, Susan M; Gallagher, Paul John; Cousins, Gráinne
Abstract : Objective: Growing evidence suggests that older adults are at an increased risk of injurious falls when initiating antihypertensive medication, while the evidence regarding long-term use of antihypertensive medication and the risk of falling is mixed. However, long-term users who stop and start these medications may have a similar risk of falling to initial users of antihypertensive medication. Our aim was to evaluate the association between gaps in antihypertensive medication adherence and injurious falls in older (≥65 years) community-dwelling, long-term (≥≥1 year) antihypertensive users. Design: Prospective cohort study. Setting: Irish Community Pharmacy. Participants: Consecutive participants presenting a prescription for antihypertensive medication to 106 community pharmacies nationwide, community-dwelling, ≥65 years, with no evidence of cognitive impairment, taking antihypertensive medication for ≥1 year (n=938). Measures: Gaps in antihypertensive medication adherence were evaluated from linked dispensing records as the number of 5-day gaps between sequential supplies over the 12-month period prior to baseline. Injurious falls during follow-up were recorded via questionnaire during structured telephone interviews at 12 months. Results: At 12 months, 8.1% (n=76) of participants reported an injurious fall requiring medical attention. The mean number of 5-day gaps in medication refill behaviour was 1.47 (SD 1.58) . In adjusted, modified Poisson models, 5-day medication refill gaps at baseline were associated with a higher risk of an injurious fall during follow-up (aRR 1.18, 95% CI 1.02 to 1.37, p =0.024). Conclusion: Each 5-day gap in antihypertensive refill adherence increased the risk of self-reported injurious falls by 18%. Gaps in antihypertensive adherence may be a marker for increased risk of injurious falls. It is unknown whether adherence-interventions will reduce subsequent risk. This finding is hypothesis generating and should be replicated in similar populations.